(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Innovation has infiltrated all everyday issues and the utilization of Information and Communication Technology (ICT) has extended the systems and methodologies. Libraries use ICT for better services and fulfilling different client needs. Libraries have changed into advanced and virtual libraries where books, diaries and magazines have changed into digital books, e-diaries and e-magazines. This has expanded the worldwide scattering of data. Electronic assets are effectively available in the remote regions. Electronic assets tackle stockpiling issues and control the surge of data.